Exporing incongruence in the funding of non-profit organisations and their expected deliverables in the Limpopo Department of Social Development, South Africa - Mudogwa, Mbavhalelo Robert (My University, 2016)
In Limpopo Province, the delivery of social welfare services is the joint responsibility of the Limpopo DSD and NPOs. The current NPO sector is organisationally configured to have strong partnerships with the public and corporate sectors due to diminished donations from individual and private donors. The Limpopo DSD conserves this beneficial partnership by providing financial support to organisations that render services that are in line with its priorities and also address the strategic objectives of the department. All these partners play a crucial role in ensuring that the poor, vulnerable and excluded people within the South African society secure a better life for themselves. The aim of this study is to determine the reasons behind the incongruence in the funding of NPOs and the services they offer to communities as expected by the Limpopo Department of Social Development in South Africa. The literature reviews concur that successful implementation of developmental social welfare services depends on role players who bring expert knowledge, skills, financial resources and commitment to achieve the desired results. A qualitative research approach was used in this research and data were gathered through the semi-structured interviews. The study proposed that delivery of social welfare services require working together in developing budget and performance reporting arrangements that meet accountability obligations and also contribute to the collective attainment of the outcome. The recommendations made were augmented by the information gathered from the interviewed respondents and were written in such a way that it can address the identified challenges if there are implemented appropriately.
Thesis (MPA.) -- University of Limpopo, 2016
Keywords: Non-profit organisations; Funding; Nonprofit organizations -- South Africa -- Limpopo; Nonprofit organizations -- Finance; Nonprofit organizations -- Economic aspects; Nonprofit organizations -- Government policy